Evaluation of Reducing Feminism on Poverty Program in East Java - Hartati Kartikaningsih; Khotibul Umam Al Awwaly; Rachman Hartono (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
Controlling is always needed in every public policies and programs, through both of monitoring and evaluation on the process, the conformability between its process and the purposes, outputs, and impacts. The aim of this research was to monitor and to evaluate the overcoming feminism on poverty program during 2018 in some cities in East Java Province, used descriptive-qualitative method. The data was collected by visiting and surveying the sites. Research locations were determined by proportional sampling method considering kinds of business process run by targeted households in each village. Two hundred and three households from twenty villages and seven cities were monitored and evaluated, which were represented about ten percent of the population. The research showed that the success rate of the program was 96.50%. as measured by the accuracy of the target (100%), the accuracy of receiving the amount of aid and its use (100%) as well as aspects of the benefit of the aid (89.49%). From the aid provided, 87.19% led to self-motivation in doing business, increasing in income, capital, and assets were 84.24%, 84.24%, 87.68% as well as environmental supporting was 88.67%. There was no similar activity from the regional government in term of equal distribution of the aid and program sustainability. The family supporting from the households ensure the success of this program.